2019
DOI: 10.1029/2018gl080446
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Interannual Variability in Distributions and Cycling of Summer Biogenic Sulfur in the Bering Sea

Abstract: In the Bering Sea, summer dimethylsulfide (DMS) and dimethylsulfoniopropionate (DMSPd and DMSPp) exhibited substantial spatial and interannual variations during 2012–2016, encompassing both cold (2012) and warm (2014 and 2016) temperature regimes. Summer average chlorophyll a, DMS, and DMSPd concentrations in the upper water increased significantly, paralleling a 1.6 °C increase in seawater temperature. High DMS/DMSPp regions in the upper 50 m at 177°E–175°W extended both north‐eastward and south‐westward, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Enhanced DMS emissions associated with sea ice loss and higher surface water temperatures have already been reported over the summertime Arctic Ocean (Galí et al, 2019;Li et al, 2019). Further sea ice loss might increase the productivity of pelagic phytoplankton (Ardyna et al, 2014;Renaut et al, 2018), and/ or seawater-atmosphere exchange, which could lead to even higher atmospheric DMS concentrations in the future.…”
Section: Conclusion and Implications For The Changing Arctic Environmentmentioning
confidence: 91%
“…Enhanced DMS emissions associated with sea ice loss and higher surface water temperatures have already been reported over the summertime Arctic Ocean (Galí et al, 2019;Li et al, 2019). Further sea ice loss might increase the productivity of pelagic phytoplankton (Ardyna et al, 2014;Renaut et al, 2018), and/ or seawater-atmosphere exchange, which could lead to even higher atmospheric DMS concentrations in the future.…”
Section: Conclusion and Implications For The Changing Arctic Environmentmentioning
confidence: 91%
“…This change in temperature might lead to an increase in F DMS from 3.0% to 22.9% if we assume the other parameters, i.e., wind speed and seawater DMS levels, remain stable. Results from a study in the subpolar region indicated that the warming of the Bering Sea resulted in a significant increase in DMS, DMSP and F DMS (Li et al., 2019). A warmer summer Arctic Ocean might have the same effect on both seawater DMS and F DMS (Gabric et al., 2005).…”
Section: Summary and Implicationsmentioning
confidence: 99%
“…Nitrate is a limiting nutrient and is decreasing on decadal timescale (Zhuang, Jin, Cai, et al., 2021) or even thousands of years (Farmer et al., 2021) in surface Arctic waters. The supply and recycling of nitrate can significantly impact primary production (Arrigo & van Dijken, 2015; Tremblay et al., 2015), marine phytoplankton cell size (Nishino et al., 2018; Zhuang et al., 2016), carbon dioxide (CO 2 ) budget (Ouyang et al., 2021; Qi et al., 2022), ocean alkalinity budget (Hu & Cai, 2011), and biogenic gas emissions (Li et al., 2019; Zhang et al., 2021) in the western Arctic Ocean. As such, the nitrate cycle in the Arctic waters has received considerable attention (e.g., Granger et al., 2013; Nishino et al., 2020; Shiozaki et al., 2018; Tremblay et al., 2011; Zhuang, Jin, Zhang, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%